(untitled) (Socio-economic relations in the digital society, 2019)
The article is devoted to methodological issues of accounting and tax accounting of bill transactions. Considered the relevance of the use of promissory notes as means of payment between enterprises. It is proved that a large number of details and special design requirements increase the danger of recognition of the bill void and the possibility of cancellation, and present it for payment. Th e positive role of bill operations because the bill does not depreciate, reduce the requirement for cash. Determined that the legal-normative base of bill circulation in Ukraine requires further improvement taking into account international practices.Th e study of the model of bill transactions with the use of methods of their accounting on practical examples. The latest changes introduced by the Tax code on taxation of bill transactions, the appropriate examples are given.